VOLUNTARY DISCLOSURE ON PT SEMEN INDONESIA TBK: LEGITIMACY CRISIS ON REMBANG PLANT CONSTRUCTION - Gentiga Muhammad Zairin; Elvia R. Shauki (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
This study aims to evaluate how the legitimacy strategy was carried out by PT Semen Indonesia Tbk to repair the legitimacy due to the construction of the Rembang plant which was suspected of damaging the environment. Research problems arose due to inadequate company disclosures, resulting in a series of protests. This research has a contribution to understanding further how the company's strategy in facing the crisis of legitimacy. This research also uses web-based disclosure data and is processed with Nvivo 12 Pro software that has never been done before. This research uses legitimacy theory, especially strategies to repair legitimacy. This study uses case studies with triangulation of qualitative data and quantitative data, all of which are secondary data. Qualitative data in this study is the result of data processing using NVivo 12 Pro software from disclosure media such as annual reports, sustainability reports, websites, online-based newspaper, and corporate social media accounts. Quantitative data in this study include the number of words, number of sentences, and percentage of disclosures. The findings in this study were the strategy of